Analisis Persepsi dan Preferensi Masyarakat Muslim dan Non-Muslim terhadap Pemberian Label Syariah pada Bank NTB Syariah di Pulau Lombok (Studi di Kota Mataram) - Sari, Indah Firgina; Putri, Selly Febriana; Azkar, Muh. (Jurnal Ilmiah Global Education, 2024)
This research aims to find out how tourists respond to tour guides in the Sade traditional tourist village, Rembitan village, Pujut sub-district, Central Lombok. This research uses a qualitative approach method and the type of data used is descriptive qualitative and the data sources used are primary data and secondary data. Then data collection techniques use interviews, observation and documentation. Checking the validity of the data uses extended participation, triangulation, and peer checking. The data analysis technique in this research involves carrying out several stages, namely data collection, reduction, data presentation and drawing conclusions. The results obtained in this research are that tourists' responses to Sade traditional tour guides are very positive. Tour guides treat and provide good service to tourists who visit during the tour. The tour guide is very knowledgeable about information about traditional Sade tourist destinations, because the tour guide is a native of Sade hamlet. The tour guide's knowledge and attitude includes aspects of competence, showing self-confidence and a friendly attitude towards tourists. However, regarding the ability to communicate in foreign languages, not all tour guides can communicate well, there are still tour guides who are hampered by speaking English due to the minimal level of education they have taken.